2008
DOI: 10.1103/physrevb.78.014205
|View full text |Cite
|
Sign up to set email alerts
|

Orientational correlations in high-pressure fluid oxygen and nitrogen

Abstract: High-pressure x-ray diffraction measurements for supercritical fluid oxygen at 0.9, 1.2, 4.3, and 5.2 GPa and for supercritical fluid nitrogen at 2.5 GPa have been carried out at room temperature by using synchrotron x-ray diffraction. The structure factors have been interpreted by means of the reverse Monte Carlo method. Site-site and center-center radial distribution functions and relative orientations of molecular axes as a function of distance between molecular centers have been calculated from the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The existence of a polymeric liquid would be unambiguously evidenced by structure factor measurements. So far this information is limited on fluid nitrogen to 2.5 GPa at ambient temperature [12]. Extending the structural investigation into the megabar range and under a few thousand kelvin temperature represents a formidable technical challenge.…”
mentioning
confidence: 99%
“…The existence of a polymeric liquid would be unambiguously evidenced by structure factor measurements. So far this information is limited on fluid nitrogen to 2.5 GPa at ambient temperature [12]. Extending the structural investigation into the megabar range and under a few thousand kelvin temperature represents a formidable technical challenge.…”
mentioning
confidence: 99%
“…There is a good correspondance between this S mol (Q) and the one we determined at 1 GPa, 800 K (ρ = 24.6 ± 1.1 molecules.nm −3 ), except that the latter has broader peaks, which is likely due to the effect of the higher temperature. The shape of S mol (Q) is at first glance, very similar to that of a liquid with no or weak orientational correlations such as H 2 [26,59], N 2 [60,61] and O 2 [61,62]. In dense monatomic liquids it is empirically found that the position of the maximum of the FDP, Q M is related to the density ρ through the relation Q M 4.4(4πρ/3) 1/3 [63], and thus (Q M /Q M 0 ) 3 ρ/ρ 0 where Q M 0 and ρ 0 correspond to a reference state.…”
Section: A Experimentsmentioning
confidence: 83%
“…Molecular pairs were classified by the number of ligands, belonging to one and the other of the two molecules between these planes; this way, six "original" orientational groups arise. 17,18 It was demonstrated that well recognizable arrangements can easily be monitored such as "parallel"/"antiparallel," "T-shaped" or "chainlike. ͑2͒ Second, the two types of ligands ͑hydrogen and halogen atoms͒ were distinguished; note that this is our new extension to the original method.…”
Section: B Calculation Of Orientational Correlation Functionsmentioning
confidence: 99%